Shell Malaysia grants for sustainable projects - The, Sun (The Sun, 2014)
ENVIRONMENTAL sustainability relies on conditions that facilitate harmony between humans and the natural world. Due to industralisation, the symbiotic relationship has been detrimentally altered. Hence, businesses are increasingly expected toto make vital and necessary changes to its practices. To make a great impact, bigger organisations are consequently exhorted to support non-governmental organisations (NGO) in their environmental saving efforts.